Pulmonary function after segmentectomy versus lobectomy in patients with early-stage non-small-cell lung cancer: a meta-analysis. Issue 9 (September 2021) - Wang, Xinxin; Guo, Haixie; Hu, Quanteng; Ying, Yongquan; Chen, Baofu
Objective: Segmentectomy is widely performed for early-stage lung cancer. However, the effects of segmentectomy versus lobectomy on pulmonary function remain unclear. We performed a meta-analysis with the aim of comparing segmentectomy and lobectomy in terms of preservation of pulmonary function in patients with early-stage non-small-cell lung cancer (NSCLC). Methods: We conducted a literature search of PubMed using the terms 'pulmonary function' AND 'segmentectomy' AND 'lobectomy'. The primary outcomes of interest were the forced expiratory volume in 1 second (FEV1), FEV1 as percent of predicted (%FEV1), change in FEV1 (Δ%FEV1), and the ratio of postoperative to preoperative FEV1. Results: Thirteen studies comprising 2027 patients met the inclusion and exclusion criteria and were included for analysis, including 787 patients in the segmentectomy group and 1240 patients in the lobectomy group. Patients in the segmentectomy group showed significantly better preservation of FEV1 and %FEV1 compared with the lobectomy group. The reduction in FEV1 after surgery was significantly less in the segmentectomy group compared with the lobectomy group, and Δ%FEV1 was significantly higher in the segmentectomy group than in the lobectomy group. Conclusion: Segmentectomy results in better preservation of pulmonary function compared with lobectomy in patients with early-stage NSCLC.